Implication of good corporate governance and leverage on earnings management - hendra, joni; Koesharjono, Hery; Priantono, Seger (Universitas Pendidikan Ganesha, 2018)
Company management (agent) is the party most concerned to practice earnings management to deceive the users of financial statements so that management gain private gain (obtaining privat gains). In addition, firms with high leverage ratios are influential in performing earnings management practices because the company is in default. The existence of the principle of good corporate governance is expected to minimize earnings management resulting in financial statements do not describe the fundamental value of the company actually.The study aims at stating wheader is proves significant influence between the institutional ownership, the composition of independent commissioners, the size of the board of directors, the size of the company and the leverage on earnings management.The results of research on non-bank companies listed in LQ 45 in Indonesia Stock Exchange year 2013-2016 show that partially the composition of independent commissioners, firm size and leverage have a positive effect on earnings management. When tested simultaneously indicate that instisional ownership, composition of commissioner independent, the composition of the board of directors, the size of the company and leverage have a significant effect onÂ earnings management. Â The size of the company is a research variable that has a dominant influence on earnings management, because the larger the size or scale of the company it will be easier for the company in obtaining funding sources, both internal and external.